Safety of Simultaneous Hepatectomy and Splenectomy in the Treatment of Hepatocellular Carcinoma Complicated with Hypersplenism: A Meta-analysis - Xuefeng Liu; Zhiqiang Chen; Meng Yu; Wei Zhou; Xuting Zhi; Tao Li (Gastroenterology Research and Practice)
Background. We conducted this meta-analysis to compare the efficacy and safety of simultaneous hepatectomy and splenectomy (HS) with hepatectomy alone (HA) in patients with hepatocellular carcinoma (HCC) and hypersplenism. Materials and Methods. A systematic search was conducted in PubMed, Embase, Cochrane Library, and Wanfang Data through March 1, 2018, with no limits. Two investigators independently screened all retrieved studies. The investigators of the original publications were contacted if required information was absent. All the included studies were managed by EndNote X7. Quality assessment of the included studies was performed using a modified Newcastle-Ottawa Scale judgment. Extracted data for each endpoint were analyzed by using STATA 12.0 software. Results. Thirteen studies, including a total of 1468 patients, comparing the effects of HS with HA were pooled in this meta-analysis. Outcomes including postoperative complications, perioperative mortality, intraoperative blood transfusion, and albumin (ALB) content at postoperation day (POD) 7 did not differ significantly between the two groups. Simultaneous approaches significantly promoted 1-, 3-, and 5-year disease-free survival (DFS) rates and overall survival (OS) rates, prolonged operation time, aggravated intraoperative blood loss, increased white blood cell (WBC) and platelet (PLT) counts at POD 7, and lowered total bilirubin (T-Bil) contents at POD 1 and 7. Conclusion. Compared to HA, HS is safer and more effective in ameliorating liver function and improving survival of HCC patients complicated with hypersplenism. This trial is registered with CRD42018093779.